Economic and social progress in Latin America : natural resources - Inter-American Development Bank.; David Rockefeller Center for Latin American Studies (Washington, D.C. : Inter-American Development Bank, 1983)
This report consists of three parts. The first comprises six chapters on natural resources: an overview, agricultural land resources (soils), water, forestry, fisheries, and minerals (fuel and non-fuel). The second part deals with recent developments in Latin America, it contains two sections: one covers the Latin American economy in adjustment in 1982, and the other examines recent economic trends, economic policies, and short-and-medium term outlook in each of the 25 Latin American and Caribbean member countries of the Inter-American Development Bank. The third part updates information presented in earlier reports.
Includes bibliographical references.
ne 25/01/2019
Loans
Keywords: Economic history; Social conditions; Latin America